Rancang Bangun Prototype Deteksi Emergency Kondisi Pasien Penyakit Jantung Berbasis Sistem Benam - Adi Siswanto; A Sumarudin (Jurnal Teknologi Terapan, 2016)
Vital signs can be seen human health than body temperature, breathing, blood pressure, and pulse. In this study, designed a prototype monitoring the health condition of the human heart Microcontroller-based devices using GPRS connection to be made in the form of a small box that consists of two measurement points. The steps taken to design a monitoring system jatung human health is to design a system of hardware and software. The sensor used is Pulse Sensor and IC-LM35 spread across two measurement points. These sensors as detection of heart rate, and changes in body temperature, and heart rate measurement results and the temperature will be read and processed in the microcontroller-based Arduino and the measurement results will be stored in SDcard to log data. If there is a weakening of the heart rate in humans this device will send an emergency signal to the server that is the hospital, then the hospital will conduct an emergency response to pasienya. The results of the measurement of body temperature has an error rate of 0.73% and heart rate measurement with ECG sensor error rate of 3% and with manual measurement error of 2%.